Pelapisan (Edible Coating) Kitosan Cangkang Bekicot terhadap Mutu Fisikokimia Terung Belanda (Solanum betaceum) - Humairah, Dwina Angelina; Ridwanto, Ridwanto; Dalimunthe, Gabena Indrayani; Pulungan, Ainil Fithri (Journal of Pharmaceutical and Sciences, 2025)
Background: Chitosan, a natural polysaccharide derived from chitin deacetylation, shows potential as a natural edible coating to extend the shelf life of perishable fruits. Utilizing giant African snail (Achatina fulica) shells as a chitosan source offers a sustainable solution to reduce biological waste while replacing synthetic chemicals in food preservation. Objective: This study aimed to analyze the effectiveness of snail shell chitosan as an edible coating in maintaining the physicochemical quality of tamarillo (Solanum betaceum) during storage. Methods: Chitosan was isolated from snail shells and applied at concentrations of 10%, 20%, and 30%. Antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa was tested using the disc diffusion method. Physicochemical parameters including weight loss, moisture loss, color, pH, total acidity, vitamin C content, and total soluble solids (TSS) were measured over 7 days of storage. Results: Chitosan demonstrated strong to very strong antibacterial activity, with the largest inhibition zones at 30% concentration (29 mm for S. aureus; 33.8 mm for P. aeruginosa). The 30% chitosan treatment yielded optimal results: lowest weight loss (3.15%), moisture loss (5.75%), pH (7.72), total acidity (16.44%), and TSS (1.350). Vitamin C retention was significantly higher in the 30% chitosan group (551.47 mg/100g) compared to control (416.53 mg/100g), confirming its effectiveness in inhibiting oxidation. Conclusion: 30% snail shell chitosan proved effective as an edible coating for maintaining tamarillo's physicochemical quality, while providing a natural and sustainable solution for the food industry.